Does the Improvement of Farmers’ Digital Literacy Restrain Their Opportunistic Behavior When They Choose Pest Control Methods in Certified Agro-Products? - Xiujuan Cui; Jieyu Yang; Ziqian Fan; Yongqiang Wang (Agriculture)
Information asymmetry leads to farmers’ opportunistic behavior of disobeying pest control regulations in certified vegetable areas, but the improvement of farmers’ digital literacy has become an important means to break through the constrained dilemma of pest control information and change farmers’ pest control behaviors. Based on survey data from certified vegetable areas of Shaanxi, Gansu, and Ningxia provinces in China, this study used Heckman two-stage model to analyze the impact of the improvement of farmers’ digital literacy on opportunistic behavior in pest control. The results are as follows. Firstly, the improvement of farmers’ digital literacy can restrain their opportunistic behavior in pest control. Secondly, the improvement of farmers’ digital literacy restrain their opportunistic behavior through three paths, namely, enhancing the awareness of obeying pest control regulations for certified vegetables, reducing the cost and risk of pest control in obeying the certification standards. Thirdly, the traceable certification label plays a positive moderating role in the process of improving digital literacy to restrain farmers’ opportunistic behavior. Accordingly, this study suggests strengthening the training of farmers’ digital literacy, promoting the digitalized traceability system for certified vegetables, establishing examination mechanisms for online pesticide purchases and logistics distribution, and imposing severe penalties for opportunistic behaviors.